Standarisasi Pelayanan Terhadap Konsumen Melalui Pendidikan Komunikasi Interpersonal Berbasis Hypnosis Pada Karyawan Kebab Turki Babarafi Kota Bengkulu - Selviani, Diah; Rachayu , Imma; Nurmita, Fina; Suryani , Novi Ade; Yuniarti, Vemmy; Adidarma , Rifeldo (Universitas Dehasen Bengkulu, 2019)
This study aims to analyze the effectiveness of hypnosis-based interpersonal communication education in increasing the standardization of service to consumers at Kebab Turki Babarafi employees in Bengkulu City. Interpersonal communication education focuses on developing good communication and interaction skills between employees and consumers, while hypnosis is used as a method to increase concentration and influence employee behavior in providing better service. This study used an experimental research design with a control group and a treatment group. The treatment group will receive hypnosis-based interpersonal communication education, while the control group will not receive the intervention. Data was collected through direct observation and questionnaires given to employees and consumers before and after the intervention. Data analysis was performed using appropriate statistical methods. It is hoped that the results of this study can provide a deeper understanding of the effectiveness of hypnosis-based interpersonal communication education in increasing the standardization of service to consumers.